Gambaran Profil Hematologi Dalam 24 Jam Pertama Pada Pasien Sepsis Di Unit Neonatus RSUD Dr. Pirngadi Medan Tahun 2017-2018 - Alpa Exaudi Siahaan; Johan Christian Silaen; Leo Simanjuntak (Nommensen Journal of Medicine, 2021)
Background: Neonatal sepsis is a clinical syndrome on infants aged 28 days or more. According to WHO data on 19th April 2018, estimated 3 million newborns and 1.2 million children suffer from sepsis globally every year. Hematological profile assessment can be used as a clinical guide to diagnose sepsis and early management of patients with early onset, especially in hospitals with limited facilities and the examination data can be obtained faster. Objective: This study was aimed to determine the hematological profile in sepsis patients in neonatal unit at RSUD Dr. Pirngadi Medan. Method: This research was a descriptive cross-sectional design. The research sample was selected by total sampling. Results: The results of the study were found from 74 neonates, 44 (59.5%) were male. Neonates with normal labor were 57 (78.1%) and survived 45 (60.8%). It was found that leukocytes (76.4%), neutrophils (60%), monocytes (87.9%), and hemoglobin (40.3%) were increased. Conclusion: The hematological profile can be used as a clinical assessment of sepsis at the first 24 hours on neonates. Hematological examination found an increased leukocytes, neutrophils, monocytes, and hemoglobin in neonatal sepsis patients at the first 24 hours.